Posterior reversible encephalopathy syndrome in systemic lupus erythematosus: pooled analysis of the literature reviews and report of six new cases - Shaharir, SS; Remli, R; Marwan, AA; Said, MSM; Kong, NCT (Sage Publications Ltd, 2024)
Indexed by WOS/ Scopus